IT enabled services - Uesugi, Shiro (Springer Vienna, 2013)
As the global economy turns more and more service oriented, Information Technology-Enabled Services (ITeS) require greater understanding.  Increasing numbers and varieties of services are provided through IT.  Furthermore, IT enables the creation of new services in diverse fields previously untouched. Because of the catalyzing nature of internet technology, ITeS today has become more than "Outsourcing" of services.  This book illustrates the enabling nature of ITeS with its entailment of IT, thus contributing to the betterment of humanity.  The scope of this book is not only for academia but also for business persons, government practitioners and readers from daily lives.  Authors from a variety of nations and regions with various backgrounds provide insightful theories, research, findings and practices in various fields such as commerce, finance, medical services, government and education.  This book opens up a new horizon with the application of Internet-based practices in business, government and in daily lives.  Information Technology-Enabled Services works as a navigator for those who sail to the new horizon of service oriented economies.